(untitled) (Journal of Engineering, 2005)
Different parameters were investigated to evaluate their effect on the process removal efficiency of COD and color, by using different H₂O concentration, UV power, multi-step addition of HO2, and air bubbling. As a result, the color can be removed completely within 20 minutes, and the COD removal of approximately 90% can be achieved within 40 minutes of UV illumination. This process favors the H₂O, addition in one step rather than in four steps. Supply of oxygen does not enhance the process removal efficiency. The overall result indicates that the operating cost (chemical and electricity) to reduce the COD to below 80 mg/l is 0.93 US/m3